2011
DOI: 10.1124/jpet.111.185124
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Characterization of Knockin Mice with Mutations M287L and Q266I in the Glycine Receptor α1 Subunit

Abstract: We used behavioral pharmacology to characterize heterozygous knockin mice with mutations (Q266I or M287L) in the ␣1 subunit of the glycine receptor (GlyR) (J Pharmacol Exp Ther 340: 304 -316, 2012). These mutations were designed to reduce (M287L) or eliminate (Q266I) ethanol potentiation of GlyR function. We asked which behavioral effects of ethanol would be reduced more in the Q266I mutant than the M287L and found rotarod ataxia to be the behavior that fulfilled this criterion. Compared with controls, the mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 42 publications
6
48
0
Order By: Relevance
“…The use of GLIC as a template for homology modeling of GlyR has been supported by two recent studies: 1) it was possible to combine the ligandbinding domain of GlyR with the TM domain of GLIC and obtain a functional chimera that gates in response to glycine (Duret et al, 2011); and 2) mutations in the TM domain of GLIC that made it resemble GlyR resulted in the enhancement of sensitivity to potentiation by ethanol at concentrations in the range of intoxication (Howard et al, 2011). The behavioral tests performed in these knockin mice are presented in a companion article (Blednov et al, 2012) …”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…The use of GLIC as a template for homology modeling of GlyR has been supported by two recent studies: 1) it was possible to combine the ligandbinding domain of GlyR with the TM domain of GLIC and obtain a functional chimera that gates in response to glycine (Duret et al, 2011); and 2) mutations in the TM domain of GLIC that made it resemble GlyR resulted in the enhancement of sensitivity to potentiation by ethanol at concentrations in the range of intoxication (Howard et al, 2011). The behavioral tests performed in these knockin mice are presented in a companion article (Blednov et al, 2012) …”
Section: Introductionmentioning
confidence: 84%
“…We conclude that this role of taurine is probably minimal, given that ␣1(M287L) homomeric GlyRs are insensitive to taurine, and yet the glycinergic function in heterozygous ␣1 M/L knockin mice is not as compromised as in ␣1 Q/I knockin mice (Blednov et al, 2012). The effect of ethanol on the ␣1(M287L) GlyRs expressed in oocytes showed variations in different batches of oocytes when carried out in normal buffer, at times exhibiting no differences from the WT, and at other times, a slight reduction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral characterizations of GlyR KI mice Blednov et al, 2012), including D80A homozygotes (Hirzel et al, 2006), have shown that impairments in GlyR function are accompanied by changes in startle responses. Here, we compared this behavior in the heterozygotic D80A KI and WT mice.…”
Section: Behavioral Tests In Glyr Ki Micementioning
confidence: 99%
“…Startle responses elicited by a series of auditory stimuli were record as previously described Blednov et al, 2012). First, mice were placed in Plexiglas holding chamber for a 5-minute acclimation period.…”
Section: Acoustic Startle Responsementioning
confidence: 99%